PETROGENESIS OF MAFIC LAYERS IN THE HOROMAN PERIDOTITE COMPLEX, JAPAN - Takazawa, Eiichi; Frey, Frederick A.; Shimizu, Nobumichi; Saal, Alberto; Obata, Masaaki (Ofioliti, 1999)
Upper mantle peridotites exposed in the earth’s crust are commonly interlayered by mafic layers such as pyroxenites and olivine gabbros (mafic granulites), which may parallel or cross-cut the foliation of the host peridotite (e.g., Nicolas and Jackson, 1982). Similar to other orogenic lherzolites and mantle xenoliths the Horoman peridotite contains two dominant types of mafic layers (Type I and Type II mafic granulites) (Niida, 1984; Shiotani and Niida, 1997; Takazawa et al., 1998). Type I layers have higher Ti and lower Cr contents than Type II layers. Both types consist of plagioclase, clinopyroxene and olivine associated with minor pargasite and opaque minerals. However these assemblages reflect subsolidus reactions occurring during uplift of the Horoman complex from upper mantle to the lower crust. In this study we present major and trace element abundances and Sr and Nd isotopic data for mafic layers in the Horoman peridotite to determine the origin of these layers, including their depth of formation, the temporal sequence of the two types.The thick Type I layers have significant intralayer compositional heterogeneity. Relative to the margins, the centers have lower Mg#, lower abundances of highly incompatible elements, higher abundances of HREE and higher 143Nd/144Nd ratios. We consider that the centers represent garnet clinopyroxenite cumulates and the margins represent melt in equilibrium with these cumulates. These melts had the isotope characteristics of MORB. On the basis of twopoint isochrons and model ages for the Sm-Nd isotopic system, we consider that the thick Type I layers formed at ca. 80 Ma.In contrast to Type I layers, the Type II layers are more homogeneous being characterized by lower abundances of incompatible elements and relative enrichments of Sr and Eu in primitive mantle-normalized patterns. Type II layers formed as plagioclase-rich cumulates in the upper mantle. Although they formed at lower pressures than Type I layers, the Type II layers have Nd isotopic systematics consistent with a 831 Ma whole-rock peridotite isochron which may indicate the age of partial melting of the Horoman peridotite (Yoshikawa and Nakamura, 1998).This evidence for ancient low pressure events in a peridotite which was recently emplaced into the crust from the garnet stability field (Ozawa and Takahashi, 1995; Takazawa et al., 1996) requires a complex pressure-temperature history for the Horoman complex. A possible scenario is (a) partial melting and crystallization in the shallow oceanic upper mantle, an event recorded by Type II layers (this study) and the Nd isotopic systematics of the peridotites (Yoshikawa and Nakamura, 1998); (b) subsidence of the complex to pressures within the stability field of garnet peridotite (Morishita and Kodera, 1998; Morishita, 1999; this study); (c) introduction of a second generation of MORB related melts at ~80 Ma which led to formation of the Type I layers as garnet clinopyroxenites (this study); (d) recent (~23 Ma, Yoshikawa et al., 1993) phlogopite-forming metasomatism that accompanied uplift from the garnet peridotite stability field into the crust (Ozawa and Takahashi, 1995; Takazawa et al., 1996).